Analisis Pengaruh Integrated Marketing Communication (IMC) Terhadap Brand Equity Dengan Kulitas Produk Sebagai Variabel Intervening Pada Bank BSI KCP Medan Iskandar Muda - Fahri Ansari Siregar; M. Lathief Ilhamy Nst (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this study was to determine the effect of integrated marketing communication on brand equity through product quality as an intervening variable at bank BSI KCP Medan Iskandar Muda. This type of research is explanatory research which explains the causal relationship between the variables through hypothesis testing. This research uses a sample of 60 respondents from bank bsi kcp medan iskandar muda. Hypothesis testing was carried out using the t test and using sobel analysis to test the intervening hypothesis. Data analysis used the partial least squares (pls) method assisted by smart pls 3.0 software to facilitate research. From the results of testing the three hypotheses that have been carried out, it can be concluded that the integrated marketing communication variable has a positive effect on the brand equity of BSI KCP Medan Iskandar Muda customers of 4.7692. The integrated marketing communication variable has a positive effect on the quality of bsi bank products of 8.988. product quality variable has a positive and significant effect on bank bsi's brand equity of 4.4666. Then seen from the value of r square shows that the magnitude of influence between variables is 0.5134 which means that product quality variables can be influenced by integrated marketing communication variables on bsi bank customers by 51.34% while the remaining 48.66% is explained by other variables that are not examined in this research. The r square value of brand equity indicates that the magnitude of influence between variables is 0.5727, which means that brand equity variables can be influenced by integrated marketing communication variables and product quality for BSI bank customers by 57.27% while the remaining 42.73% is explained by other variables that are not examined in this study.